1990
DOI: 10.1148/radiology.174.2.2404314
|View full text |Cite
|
Sign up to set email alerts
|

Renal artery stenosis: prospective evaluation of diagnosis with color duplex US compared with angiography. Work in progress.

Abstract: A prospective, double-blind comparison of color duplex sonography with angiography was performed for diagnosing renal artery stenosis in 50 kidneys in 26 patients. The major criterion for diagnosing a diameter narrowing of more than 50% was a velocity of greater than 100 cm/sec. Angiography demonstrated 10 stenoses and one occlusion in main or accessory renal arteries in seven patients. Twenty-two percent of kidneys had accessory renal arteries. Color duplex scanning helped identify 58% of the main arteries an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
68
1
4

Year Published

1998
1998
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(75 citation statements)
references
References 0 publications
2
68
1
4
Order By: Relevance
“…Some investigators report remarkable success, while others have reported dismal results in large unselected patient groups. 15,16 A recent study declared duplex ultrasound to be most valuable not only in the screening for renal artery disease but also to estimate its functional significance by means of determination of the resistive index. 17 The duplex ultrasound performance in this study, however (ie, sensitivity 97%; specificity 98%), was derived from a previous report by the same authors in a selected group of patients with a high prevalence of renovascular disease (58%).…”
Section: Discussionmentioning
confidence: 99%
“…Some investigators report remarkable success, while others have reported dismal results in large unselected patient groups. 15,16 A recent study declared duplex ultrasound to be most valuable not only in the screening for renal artery disease but also to estimate its functional significance by means of determination of the resistive index. 17 The duplex ultrasound performance in this study, however (ie, sensitivity 97%; specificity 98%), was derived from a previous report by the same authors in a selected group of patients with a high prevalence of renovascular disease (58%).…”
Section: Discussionmentioning
confidence: 99%
“…Authors, who considered a velocity > 100 cm/s as a parameter, had low accuracy indices, but a high index of inconclusive examinations, denoting individual technical limitations in the study of the renal arteries on vascular color Doppler ultrasound 8,9 .…”
Section: Discussionmentioning
confidence: 99%
“…Experienced operators can achieve sensitivities of up to 95% for the detection of RAS (24). However, US is very operator dependent and has, therefore, a relatively high interobserver variability and a low sensitivity when performed by a nonexperienced operator (25,26). Additionally, it often fails in obese patients or those with bloated small or large bowl.…”
Section: Current Position: Indications For Imaging and Imaging Technimentioning
confidence: 99%